Analysis of the Needs for Developing a Problem-Solving Model to Improve Students' HOTS Skills - Nurmawati; Purnomo, Eko Andy (Education, Science, and Technology International Conference, 2025)
This research is the initial stage of a problem-solving model development study aimed at improving students' Higher Order Thinking Skills (HOTS) in mathematics learning. The main focus at this stage is to conduct a needs analysis to determine the actual learning conditions, students' and lecturers' understanding of the mathematization and mathematical modeling processes, as well as their obstacles, expectations, and readiness for the implementation of the learning model to be developed. A questionnaire instrument was compiled based on five main indicators, and distributed to students and lecturers at universities. The data obtained will be analyzed descriptively. The method used in this study is a qualitative research method. Research data collection through questionnaires and interviews. The subjects of this study were Mathematics Education students at universities in Semarang City. The results of the study are 1). Many students have problem-solving abilities in the low and medium categories. 2). Current mathematics learning has not fully accommodated the development of students' HOTS, 3). There is a significant need to understand and implement the mathematization and modeling processes in learning. These results will be used as a basis for developing a problem-solving learning model based on mathematization and mathematical modeling. The next research is to develop a Problem-Solving Model to Improve Students' HOTS Abilities.